Experiencing through the voice in Stanislavski's psycho-physical approach. Issue 2 (2nd July 2016) - Gillett, John
Abstract: At the centre of Stanislavski's acting approach is the actor's connection with the imaginary circumstances and the action, a connection that is imaginatively experienced – not represented and illustrated – and is embodied vocally and physically to reach both "the life of the human spirit of a role" and the audience. A key part of the action for Stanislavski is verbal action. Voice and speech, though, can be technically taught as skills separate from acting process. Language can be tackled from a static, literary perspective in rehearsals. Stanislavski viewed voice and speech not as ends in themselves but as flexible, changing responses to an imaginary, dynamic reality suggested by the text. The article examines how voice may be integrated within an organic acting process and be part of an embodied experience, and also draws on the views of Stanislavski-based practitioners and contemporary neuroscience and linguistics to validate Stanislavski's psycho-physical approach and later rehearsal methods. In the final part, it gives an insight into how to integrate understanding of acting process into vocal instruction, and how to integrate voice into acting exercises and text.